Optical micro- and nanometrology in microsystems technology : 5-7 April 2006, Strasbourg, France - Gorecki, Christophe; Asundi, Amand K.; Osten, Wolfgang; The International Society for Optical Engineering (Bellingham, WA : SPIE Press, 2006)
40